The other side of Heaven 2 [videorecording (DVD)] : fire of faith - Groberg, John H.; Davis, Mitch; Gorham, Christopher, 1974-; Medlock, Natalie, 1986-; Dixon, Russell, (Actor) (Excel Entertainment Group, 2019)
Missionary John H. Groberg returns to Tonga in the '60s with his wife and their five young daughters. The Grobergs face their ultimate test of faith but are surrounded by the love and prayers of thousands of Tongans. Barriers of inter-religious strife are soon broken down as all unite in hopes of a miracle.